High Pressure Liquid Chromatography Estimation of Glipizide in Pharmaceutical Dosage Forms - Vijaya Saradhi, S.; Satya Kiran, V.; Hima Bindu, V.; Devala Rao, G. (Asian Journal of Chemistry, 2010)
A reverse phase high pressure liquid chromatographic method has been described for the estimation of glipizide in its pharmaceutical formulations using C-8 column. The mobile phase consisted of acetonitrile, methanol and buffer (7.0 mL of triethyl amine in 1000 mL of water, pH adjusted to 3.0±0.1 with orthophosphoric acid) in the ratio of 35:50. The detection was carried out at 230 nm and the linearity was found to be in the range of 0.1 to 10 μg/mL. The method is simple, precise, specific, less time consuming and accurate for the estimation of glipizide in pharmaceutical dosage forms.